Resilience Factors in Early Childhood: Islamic Values and Self-Regulation through a Mixed-Method Approach - Salsabila, Dea Amalia; Rohmah, Naili (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
This study, conducted at Raudlatul Athfal Al-Iman in Semarang City, explores resilience factors and levels among students, emphasizing the role of Islamic values in fostering resilience and self-regulation and using a concurrent embedded mixed-method approach, prioritizing qualitative data from interviews, observations, documentation, and questionnaires to explore cultural and religious influences on resilience, particularly in interactions with peers, educators, and the community. The qualitative approach provided insights into how Islamic values are internalized and expressed in children’s behaviors. At the same time, quantitative data, measured using the Child and Youth Resilience Measure (CYRM), categorized students’ resilience levels. This combination ensured a comprehensive understanding by integrating contextual depth with numerical validation. Findings revealed that Islamic practices, including istighosah, reading Iqra', memorizing Hadith (Mutiara habits), daily prayers, recitations of Asmaul Husna, and short Qur’anic surahs, significantly influence students' resilience. These activities, integrated into daily routines, help children adopt Islamic values in peer interactions and demonstrate resilience characteristics. Teachers reinforce resilience by promoting problem-solving that is aligned with Islamic teachings. Quantitative data from 30 students indicated resilience levels: 6 students were categorized as high, 19 as moderate, and 5 as low. This research highlights the potential of faith-based practices to enhance mental well-being and learning outcomes in Islamic early childhood education. While constrained by a small sample size and limited scope, it offers valuable insights into resilience-building strategies in similar contexts. Future studies should expand on integrating resilience theory and Islamic values in early education across broader settings.